Minute stitches cross-stitching as a visualization of time - Co, Hannah Shireen C.
Time, a metaphysical concept, is intangible, but it is what allows us to experience the world. This thesis tries to capture time by recording and recollecting my time over the course of a week, and then abstracting, translating, and mapping the data into something very tangible - cloth, something we touch every day, and, like time, ubiquitous. The idiom 'fabric of time'' lends itself to this visualization of our daily experience of time. Our perception of time's passage is not always by the clock - it can slow down or speed up depending on the circumstances. The malleability of the cloth allows for the stretching or compressing of time to be mirrored in the creasing and bunching of the cloth. However, this malleability contrasts against the inherent grid structure of the weave. The overlaid grid policies time into neat, universal units. A single stitch, like a single second, or a single minute, can add p into hours, days, years. I use the stitch as a unit to count time and delineate the natural and arbitrary boundaries we put around it. The unending sequence of stitches and the very act of sewing - the slow, arduous process, makes the person sewing hyper-aware of time. The work aims to make sense of the passing of time, through the sequential process of sewing and the minutes it records, and is a trace of the amount of time invested into a certain work.